Prevalence of, Antibody Response to, and Immunity Induced by Haemophilus ducreyi Hemolysin - Dutro, Susan M. (American Society for Microbiology, 1999)
Haemophilus ducreyi, the etiologic agent of chancroid, a genital ulcer disease, produces a cell-associated hemolysin whose role in virulence is not well defined. Hemolysin is encoded by two genes, hhdA and hhdB, which, based on their homology to Serratia marcescens shlA and shlB genes, are believed to encode the hemolysin structural protein and a protein required for secretion and modification of this protein, respectively. In this study, we determined the prevalence and expression of the hemolysin genes in 90 H. ducreyi isolates obtained from diverse geographic locations from 1952 to 1996 and found that all strains contained DNA homologous to the hhdB and hhdA genes. In addition, all strains expressed a hemolytic activity. We also determined that hemolysin is expressed in vivo and is immunogenic, as indicated by the induction of antibodies to hemolysin in both the primate and rabbit disease models as well as in human patients with naturally acquired chancroid. Wild-type strain 35000 and isogenic hemolysin-negative mutants showed no difference in lesion development in the temperature-dependent rabbit model. However, immunization of rabbits with the purified hemolysin protein reduced the recovery of wild-type H. ducreyi, but not hemolysin-negative mutants, from lesions. Our study indicates that hemolysin is a possible candidate for vaccine development due to its immunogenicity, expression in vitro and in vivo by most, if not all, strains, and the effect of immunization on reducing the recovery of viable H. ducreyi in experimental disease in rabbits.